ADOPSI E-COMMERCE PADA UMKM DI ERA PANDEMI COVID-19 (Studi Kasus pada UMKM di Kota Ambon) - Senda Yunita Leatemia (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2020)
Senda Yunita Leatemia, in the era of the COVID-19 pandemic, a business is required to adopt existing technology to run its business. This study aims to determine the benefits that are felt after adopting e-commerce, the technology capabilities of UMKM to adopt e-commerce, and the level of application of e-commerce adoption to UMKM. The research method in this study is a quantitative method. Data analysis method used in descriptive statistical analysis using frequency tables. The results of this study state that the benefits of e-commerce are classified in the useful category, the technology capabilities are in the low category, and the level of e-commerce adoption is in the category low.